Financial crimes in Africa and economic growth: Implications for achieving Sustainable Development Goals (SDGs) - Kingsley K. Arthur; Simplice Asongu; Peter Darko; Marvin O. Ansah; Sampson Adom; Omega Hlortu (African Governance and Development Institute (AGDI), 2024)
The current review systematically synthesizes existing literature to provide a comprehensive overview of the nature of financial crimes in Africa and their impact on economic growth. We adopted the PRISMA protocol to identify 128 papers from the Scopus database; which were analyzed using MS Excel, VOS Viewer, and R-packages (Bibliometrix). The survey reveals that financial crimes are on the rise in Africa and have gained increasing concern over the years on the part of scholars, governments and NGOs. The survey also demonstrates that most of the financial crime in Africa emanates from illicit activities such as credit card fraud, cybercrime, mobile money fraud, financial statement fraud, Ponzi scheme, bribery and corruption, public fund mismanagement, terror financing, piracy, identity fraud, tax invasion, drug trafficking, product based-fraud, burglary, trade-based money laundering, sex marketing and gambling; with the majority occurring in specific regions like Western Africa, Southern Africa and Eastern Africa. Socio-political marginalization, poverty and unemployment, weak institutional and financial regulatory systems and individual selfish interests were the major causes. Overall, the content analysis of the studies indicates that financial crimes have significant negative impacts on the economic growth of the African continent. Implications for future research and practices have been discussed.
Keywords: 330; Financial crime; financial fraud; Money laundering; Africa; Economic development; Economic growth; and Bibliometric